Rethinking the teaching of theory through Practicums: the experience of a pre-service teacher - Marcos Jesús Iglesias Martínez; María Moncho Miralles; Inés Lozano Cabezas (Universidad de La Rioja, 2019)
The gap between theoretical and practical knowledge, both fundamental in building teacher professionalization, is significantly affecting initial teacher training. Based on a qualitative approach and reflective practice, we analysed a pre-service school teacher's conceptions and beliefs on the links between theoretical knowledge and experiences lived during the Practicum. Results showed that theory continues to represent the exclusive standpoint from which actions should be governed. Moreover, we identified the need to foster a dialogical relationship between theoretical knowledge and interdisciplinary experiences provided during the Practicum. The main conclusions of this study imply that "hybrid spaces" (Zeichner, 2010) should be created to improve the relationship between both types of knowledge, theory playing a necessary role in guiding practice. It is imperative that initial teacher training integrate these "spaces" based on reflection and dialogue between all participating agents: this will allow making sense of theoretical-practical knowledge with the aim of training professionals able to observe, analyse and reflect on teaching and learning dimensions.